REPEATED INTERVENTIONS AFTER TOTAL REPAIR IN PATIENTS WITH TETRALOGY OF FALLOT - Romaniuk, O.M.; Rudenko, N.M. (World of Medicine and Biology, 2025)
Tetralogy of Fallot occurs in 3.5 % of all congenital heart defects. The total correction consists in eliminating the obstruction of the right ventricular outflow tract using two main techniques: transannular patch and valve-sparing repair – non-transannular patch. The long-term results of 1352 radical corrections of tetralogy of Fallot performed at the Ukrainian Cardiac Center from 1999 to 2022. The the median age of patients at the time of surgery was 9.8 months. The use of transannular patch was 64.2 %, and Non-transannular patch – 35.8 %. The total mortality was – 3.46 %. Reinterventions were performed in 213 (16.5 %) patients. The most procedures were associated with pulmonary artery valve insufficiency (55.5 %) and right ventricular outflow tract obstruction (40.7 %). Analysis of risk factors showed that the use of transannular patch is an independent risk factor for repeated operations (r=0.726, p